Korean Multiculturalism and the Emergence of Foreign Brides in South Korea - Lee, Min; Govindasamy, Geetha; Tan, Soo Kee (WILAYAH: The International Journal of East Asian Studies, 2025)
Multiculturalism is a universal trend in most countries that have an influx of migrants. However, it is a recent phenomenon in South Korea which prides itself of having a homogenous society. This article examines multicultural marriages and discusses the emergence of female marriage migrants who are in part responsible in creating a multicultural Korea. This research uses a qualitative approach where existing literature, databases and other previously published materials have been used to gain a deeper understanding of the relationship between foreign brides who have come into Korea through multicultural marriages which in the long run has contributed greatly to forming a multicultural Korean society. Despite several challenges, findings suggests that female marriage migrants are now acknowledged as one of the catalysts in the transformation of Korean society from a homogenous one to that of a multicultural entity. This is seen in the various laws adopted to integrate foreign brides and their offspring. However, though this is happening, the process of integration between foreign brides and the Korea pubic in general has a long way to go.